2022
DOI: 10.1002/anie.202210579
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Supramolecular Charge‐Transfer Interactions in the Solid State using Compressible Macrocyclic Hosts

Abstract: Modulating intermolecular charge‐transfer (ICT) interactions between specific donor and acceptor species in host–guest systems is a big challenge and full of research value in supramolecular chemistry and materials science. In this work, a strategy to modulate the supramolecular ICT interactions in the solid state is developed by compressing the binding cavity of a macrocyclic host named perethylated leaning pillar[6]arene (p‐EtLP6). The solid‐state ICT affinities of p‐EtLP6 toward multi‐types of electron‐defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…Very recently, we proposed a cavity-compressing strategy to stabilize the host-guest CT affinities in the solid state by the skeleton isomerism of a pillarene-derived novel macrocyclic arene, namely leaning pillar [6]arene (H15, Figure 12a). [22] It was found that, in the crystalline state, H15 with simplex para-bridged unit connection mode (referred to as p-H15) can initially bind DNB, DFN, and 4-nitrobenzonitrile (NBN) to form 1 : 1 inclusion complexes with weak CT signals, respectively. Significantly, these solid-state host-guest CT affinities could be remarkably enhanced by the transformation of the original para-bridged macrocyclic backbone into a hybrid meta-and para-bridged isomeric form (m-H15).…”
Section: Host-isomerism-induced Host-guest Ct Enhancementmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, we proposed a cavity-compressing strategy to stabilize the host-guest CT affinities in the solid state by the skeleton isomerism of a pillarene-derived novel macrocyclic arene, namely leaning pillar [6]arene (H15, Figure 12a). [22] It was found that, in the crystalline state, H15 with simplex para-bridged unit connection mode (referred to as p-H15) can initially bind DNB, DFN, and 4-nitrobenzonitrile (NBN) to form 1 : 1 inclusion complexes with weak CT signals, respectively. Significantly, these solid-state host-guest CT affinities could be remarkably enhanced by the transformation of the original para-bridged macrocyclic backbone into a hybrid meta-and para-bridged isomeric form (m-H15).…”
Section: Host-isomerism-induced Host-guest Ct Enhancementmentioning
confidence: 99%
“…For example, macrocyclic hosts themselves can simultaneously act as donor and acceptor components in an intermolecular CT system (Scheme 1a,b). [14–16] Besides, crystalline CT complexes could also be constructed using macrocyclic hosts and guest species with opposite electronic character (Scheme 1c) [18–24] . More importantly, such a combination of macrocyclic hosts and CT crystal/co‐crystal engineering provides a convenient and modular strategy to construct D‐A type functional materials with smart stimuli‐responsiveness [14–20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Consequently, host-guest recognition has attracted great attention. So far, the focus has covered five classical macrocyclic host molecules, [16][17][18][19][20][21] namely crown ethers, cyclodextrins (CDs), calix[n]arenes, cucurbit[n]urils (CB[n]s), and pillar[n]arenes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the use of identical precursors, variable stoichiometry co-crystals often display solid-state superstructures that are unique and difficult to predict a priori. This has made them of interest to the pharmaceutical industry, in part because of the new intellectual property they can embody. Here, we show that pillararenes, an important class of building blocks in solid-state supramolecular chemistry, can be used to prepare variable stoichiometry co-crystals. As detailed below, we have found that combinations of perethylated pillar[5]­arene ( EtP5 ) or pillar[6]­arene ( EtP6 ) with tetracyanobenzene ( TCNB ) (Figure ) allow access to a series of organic charge-transfer co-crystals with different stoichiometric ratios.…”
Section: Introductionmentioning
confidence: 99%